2006
DOI: 10.1136/jmg.2005.039172
|View full text |Cite
|
Sign up to set email alerts
|

Letting the family know: balancing ethics and effectiveness when notifying relatives about genetic testing for a familial disorder

Abstract: Objective: To increase the awareness among at risk relatives of the availability of genetic testing for a familial disorder while respecting their autonomy and privacy. Methods: This was a comparison of preintervention and postintervention cohorts of families carried out in a state wide clinical service providing genetic counselling and testing for people at risk of familial adult onset cancer. Unaffected relatives who were not clients of the service in 74 kindreds with familial mutations causing familial brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
170
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(176 citation statements)
references
References 23 publications
4
170
2
Order By: Relevance
“…This theme comprises two papers 30,31 presenting studies in which services/professionals directly contact the family members potentially at-risk. The two papers explore the acceptability and feasibility of direct contact by genetic services to high-risk relatives informing them about the availability of genetic counselling and testing.…”
Section: Discussionmentioning
confidence: 99%
“…This theme comprises two papers 30,31 presenting studies in which services/professionals directly contact the family members potentially at-risk. The two papers explore the acceptability and feasibility of direct contact by genetic services to high-risk relatives informing them about the availability of genetic counselling and testing.…”
Section: Discussionmentioning
confidence: 99%
“…The exception is the method of direct contact from the genetics service to at-risk family members by posting generic letters warning of increased risk of cancer. 36 Although this method of direct contact results in a significantly increased uptake of clarification of genetic status by at-risk family members, 36 other research suggests that probands and consultands prefer to disseminate genetic information to family members rather than relying on the genetics service. 21 A follow-up consultation where familial communication issues are addressed seems a logical and practical method given the results from these interviews.…”
Section: Box 7 Family Members' Awarenessmentioning
confidence: 99%
“…Similarly, studies of cascade testing for hereditary cancers describe these two approaches of making contact with relatives. 31,32 A comparison of standard clinical practice and an intervention that included greater emphasis on, and assistance with, family communication showed that with additional follow-up genetic counselling, greater proportions of relatives contacted genetic services. 33 Although the studies described above can suggest how to better support families of children diagnosed with CF through NBS, an important difference is that the genetic information in the present study relates to reproductive risk rather than personal health.…”
Section: N¼716mentioning
confidence: 99%